Early unexpected failure of a vitamin E-infused highly cross-linked polyethylene liner: A case report. Issue 41 (15th October 2021) - Kim, Kyeong Baek; Lee, Sang-Min; Moon, Nam Hoon; Do, Min Uk; Shin, Won Chul
Abstract: Rationale: Total hip arthroplasty (THA) with a polyethylene (PE) liner is 1 of the most effective and successful treatment strategies for end-stage hip disorders. Vitamin E-infused highly cross-linked polyethylene is theoretically known to prevent failure due to oxidative degradation in the body, and is resistant to wear; therefore, successful long-term survival of THA is expected. Patient concerns: In June 2019, approximately 1.5 years after THA, the patient sat down and stood up without any specific issue; however, an unusual bullet sound occurred around the left hip joint. Since then, his discomfort persisted, and he was admitted to the emergency department. Diagnosis: Plain radiography and metal artifact reduction computed tomography performed in the emergency department revealed eccentric elevation of the prosthetic femoral head and suspected PE liner failure. Intervention: Revision surgery was performed for modular component exchange. To reduce the dislocation risk without performing cup exchange, conversion to dual-mobility articulation was performed. Outcomes: During the regular follow-up post-surgery, the patient could perform daily life activities without any discomfort, and dislocation was not observed. At 2 years postoperatively, no significant changes were observed in the radiographic images. Lessons: This case report presents an unexpected failure of THA due to superior rim fracture and excessive wear at the locking mechanism of the vitamin E-infused highly cross-linked polyethylene liner. This is an interesting case, as early PE liner failure occurred without strong labor intensity or trauma. A modular component exchange was performed with a dual-mobility bearing, and no issues were observed approximately 2 years after the reoperation. Therefore, third-generation highly cross-linked polyethylene liners can also cause early failure without a clear cause, and this case report highlights the necessity of considering several strategies for reoperation. Study Design: Case report.